1998
DOI: 10.1177/135050849851002
|View full text |Cite
|
Sign up to set email alerts
|

Managing Masculinity in Contemporary Organizational Life: A Managerial Project

Abstract: This paper seeks to theorize managerial discourses and practices in terms of their effects upon sexuality, intimacy and power in organizations. While accepting the real and immediate gendered material and social inequalities that are reinforced by the recent resurgence of unadulterated `free market' capitalism, the authors focus here on certain limited aspects of femininity and masculinity that are important for an understanding of gender identity and sexuality. Acknowledging the multiplicity of masculinities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(202 citation statements)
references
References 14 publications
6
193
1
2
Order By: Relevance
“…In a similar vein, Alvesson (1998) has shown how men working in the 'feminized' context of an advertising agency, where creativity and sensitivity in relationships were required, re-activated a traditional masculinity through a sexually appraising and subordinating 'gaze' of women. Managerialist discourses of targets, accountability and control, culturally coded masculinity (Kerfoot and Knights, 1998), have been found to drive many practices in the 'feminized' service and caring professions (Bolton, 2007;Brannen, 2005;Broadbridge, 2010b;Korczynski, 2001) -suggestive of a re-masculinization of emotional labour skills . Thus, as Korczynski (2001) suggests, the emotional labour of front line service workers such as in call centres (and also in retailing and hospitality) is being harnessed and controlled by management through 'masculine' practices involving targets, observation systems and remote monitoring in order to deliver a 'quality service'.…”
Section: Masculinity and The 'Re-masculinization' Of Managementmentioning
confidence: 99%
“…In a similar vein, Alvesson (1998) has shown how men working in the 'feminized' context of an advertising agency, where creativity and sensitivity in relationships were required, re-activated a traditional masculinity through a sexually appraising and subordinating 'gaze' of women. Managerialist discourses of targets, accountability and control, culturally coded masculinity (Kerfoot and Knights, 1998), have been found to drive many practices in the 'feminized' service and caring professions (Bolton, 2007;Brannen, 2005;Broadbridge, 2010b;Korczynski, 2001) -suggestive of a re-masculinization of emotional labour skills . Thus, as Korczynski (2001) suggests, the emotional labour of front line service workers such as in call centres (and also in retailing and hospitality) is being harnessed and controlled by management through 'masculine' practices involving targets, observation systems and remote monitoring in order to deliver a 'quality service'.…”
Section: Masculinity and The 'Re-masculinization' Of Managementmentioning
confidence: 99%
“…In alignment with increasing economic globalization and neo-liberalism, transnational business masculinity is often considered the globally dominant form of masculinity (Connell 1998, Connell andWood 2005). Business masculinity is characterized by authority (or control over subordinates) based on the impersonal and technical rationality of management (Kerfoot and Knights 1998). Although not dominating all societal domains, 'local' masculinities need to be analyzed in relation to the global dominance of this upper-middle-class definition of masculinity (Knoppers and Anthonissen 2005), something which few studies have done (Beynon 2002).…”
Section: Theorizing Gendermentioning
confidence: 99%
“…Shaw and Hoeber (2003) behind the title ''A Strong Man is Direct, and a Direct Woman is a Bitch'' have underlined that when a man adopts ''masculine traits'' he is strong and when a woman does the same, she is a ''bitch''. So, discourses of masculinity, often linked to leadership roles and men, are influential in sport organisations and can serve to undermine discourses of femininity that are frequently associated with subordinate roles and women (Hovden, 2005;Kerfoot & Knights, 1998;Knights & Kerfoot, 2004). However, a poststructuralist perspective can develop a new knowledge for understanding gender differences and disrupting the binary opposition of feminine and masculine.…”
Section: Gendering Management and Post-structuralismmentioning
confidence: 99%
“…This discourse can be congruent with an approach to human resource management in which managers see them as acting in the best interests of the organisation by adopting communication skills (Kerfoot & Knights, 1998;Knoppers & Anthonissen, 2008). Wacjman (1998), who studied male and female managers in five multinational companies, found that the emphasis on interaction abilities has meant that male managers have added these skills to their repertoire so that women are not really needed to contribute these skills to organisations.…”
Section: Correspondence Analysismentioning
confidence: 99%